2016
DOI: 10.1891/1052-3073.27.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Use of Financial Planners and Portfolio Performance

Abstract: Using modern information economics as the conceptual framework and data from the 2013 Survey of Consumer Finances, this study adopts a decomposition technique to explore the relationship between the primary information source used by U.S. investors and their household investment portfolio performance. The sample includes households with investable assets and those whose primary information source is financial planner or self-directed sources. Households that received large amounts of inheritance or gifts withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 74 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…Demographic factors, such as gender, race/ethnicity, education and employment status, have shown a consistent trend in their association with stock ownership (Barasinska and Sch€ afer, 2018;Joshi and Bayra, 2017;Shin et al, 2020;Sivaramakrishnan et al, 2017). Other investors' personal characteristics, such as expected income certainty and expected investment time horizon, also played a role in their decisions to invest in stocks (Lei, 2019;Lei and Yao, 2016;Rieger et al, 2021;Shin and Kim, 2018).…”
Section: Variablesmentioning
confidence: 96%
“…Demographic factors, such as gender, race/ethnicity, education and employment status, have shown a consistent trend in their association with stock ownership (Barasinska and Sch€ afer, 2018;Joshi and Bayra, 2017;Shin et al, 2020;Sivaramakrishnan et al, 2017). Other investors' personal characteristics, such as expected income certainty and expected investment time horizon, also played a role in their decisions to invest in stocks (Lei, 2019;Lei and Yao, 2016;Rieger et al, 2021;Shin and Kim, 2018).…”
Section: Variablesmentioning
confidence: 96%
“…Recent studies have started to investigate the value of financial advice from financial professionals. Lei and Yao (2016) found that American households who used financial planners had better performance in their investment portfolios. Similarly, Shin et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies have started to investigate the value of financial advice from financial professionals. Lei and Yao (2016) found that American households who used financial planners had better performance in their investment portfolios. Similarly, Shin et al (2020) found that people who worked with financial planners to manage their financial assets had more diversified investment portfolios than did those who did not work with financial planners.…”
Section: The Importance Of Financial Advicementioning
confidence: 99%
“…Some studies, however, examine the role of an investment advisor in individuals' financial life by evaluating their portfolio performance. Findings from these studies were controversial (Lei & Yao, 2016). While there are many potential reasons for this controversy, it is apparent that their analyses are based on different sampling techniques and some samples are not representative of the underlying population.…”
Section: Introductionmentioning
confidence: 99%